2019
DOI: 10.1098/rspb.2019.0841
|View full text |Cite
|
Sign up to set email alerts
|

Development of homeothermic endothermy is delayed in high-altitude native deer mice ( Peromyscus maniculatus)

Abstract: Altricial mammals begin to independently thermoregulate during the first few weeks of postnatal development. In wild rodent populations, this is also a time of high mortality (50–95%), making the physiological systems that mature during this period potential targets for selection. High altitude (HA) is a particularly challenging environment for small endotherms owing to unremitting low O 2 and ambient temperatures. While superior thermogenic capacities have been demonstrated in adults o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 58 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…There can be strong directional selection for increased thermogenic V̇O 2max at high altitude ( Hayes and O’Connor, 1999 ), which has led to evolved increases in thermogenic V̇O 2max in hypoxia in high-altitude deer mice compared to low-altitude deer mice and white-footed mice ( P. leucopus , a congeneric species that is restricted to low altitudes; Cheviron et al, 2012 , 2013 , 2014 ; Lui et al, 2015 ; Tate et al, 2017 , 2020 ). Differences in thermogenic V̇O 2max and in various respiratory and metabolic traits that underlie it become apparent ~2–3 weeks after birth in comparisons between high- and low-altitude mice raised in normoxia ( Robertson et al, 2019 ; Robertson and McClelland, 2019 ; Ivy et al, 2020 ; West et al, 2021a ). However, although the effects of adult acclimation to hypoxia on thermogenic V̇O 2max and its underlying determinants have been described ( Lui et al, 2015 ; Lau et al, 2017 ; Tate et al, 2017 , 2020 ), and life-long exposure to high altitude has been shown to increase thermogenic V̇O 2max ( Chappell et al, 2007 ), the specific effects of hypoxia exposure during pre-natal and post-natal development has not been resolved.…”
Section: Introductionmentioning
confidence: 99%
“…There can be strong directional selection for increased thermogenic V̇O 2max at high altitude ( Hayes and O’Connor, 1999 ), which has led to evolved increases in thermogenic V̇O 2max in hypoxia in high-altitude deer mice compared to low-altitude deer mice and white-footed mice ( P. leucopus , a congeneric species that is restricted to low altitudes; Cheviron et al, 2012 , 2013 , 2014 ; Lui et al, 2015 ; Tate et al, 2017 , 2020 ). Differences in thermogenic V̇O 2max and in various respiratory and metabolic traits that underlie it become apparent ~2–3 weeks after birth in comparisons between high- and low-altitude mice raised in normoxia ( Robertson et al, 2019 ; Robertson and McClelland, 2019 ; Ivy et al, 2020 ; West et al, 2021a ). However, although the effects of adult acclimation to hypoxia on thermogenic V̇O 2max and its underlying determinants have been described ( Lui et al, 2015 ; Lau et al, 2017 ; Tate et al, 2017 , 2020 ), and life-long exposure to high altitude has been shown to increase thermogenic V̇O 2max ( Chappell et al, 2007 ), the specific effects of hypoxia exposure during pre-natal and post-natal development has not been resolved.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced aerobic performance under hypoxia is associated with increased survivorship in free‐ranging mice at high elevation (Hayes & O'Connor, 1999) and is associated with plastic and genetically based modifications across the O 2 transport pathway (Ivy & Scott, 2015; Schweizer et al, 2019; Schweizer et al, 2021; Storz et al, 2019; Storz & Cheviron, 2021; Storz & Scott, 2019). Research into the ontogeny of these differences has only just begun, but some components of the unique physiology of highlanders are clearly manifest within the first few weeks of life (e.g., onset of endothermy, increased blood‐O 2 affinity, development of hypoxic ventilatory response; Ivy et al, 2020, 2021; Robertson et al, 2019; Velotta et al, 2020). The plastic responses to hypoxia also differ between highland and lowland mice.…”
Section: Introductionmentioning
confidence: 99%
“…Whether high-altitude deer mice have also reduced the routine demands for O 2 and metabolic fuels is less clear, but such reductions could be highly advantageous when considering that in some instances food availability may also be limited at high altitudes [37]. The ontogenetic development of endothermy is delayed in highaltitude deer mice [38][39][40], suggesting that metabolic demands of thermogenesis are reduced in early post-natal life stages. Whether they also exhibit strategies to reduce the metabolic demands of thermogenesis and body temperature regulation in later life remains unresolved.…”
Section: Introductionmentioning
confidence: 99%